Biliary cystadenoma a case report - Tandur, Amarjeet E.; Rajagopal, Solaimuthu; Mishra, Rahul K.; Bhandarwar, Ajay H.; Baradwaj, Guru; Pathe, Bhushan (International Surgery Journal, 2021)
Biliary cystadenoma (BCA) is a rare cystic neoplasm of liver with malignant potential and female predominance, mostly asymptomatic that will lead to late identification. BCAs are mostly do not communicate with Biliary tract but communication was reported in some studies, BCA has higher rate of recurrence after incomplete removal so the standard management is complete resection or partial hepatectomy. We report a case of BCA in 72-year aged female with ECOG score 3. Computed tomography showed BCA involving segment II, III, IV and VIII of liver without any malignant features, which was treated with laparoscopic deroofing with omentopexy and no recurrence at 1 year follow up. We used indocyanine green-fluorescent image to look for biliary communication. This study aims to report that minimal accesses surgery with deroofing and omentopexy can be alternative treatment for BCA without any malignant features in a poor performance status and use of Indocyanine green-fluorescent image to avoid biliary injury and rule out communication.